2022
DOI: 10.3390/s22186746
|View full text |Cite
|
Sign up to set email alerts
|

Visual Cues for Turning in Parkinson’s Disease

Abstract: Turning is a common impairment of mobility in people with Parkinson’s disease (PD), which increases freezing of gait (FoG) episodes and has implications for falls risk. Visual cues have been shown to improve general gait characteristics in PD. However, the effects of visual cues on turning deficits in PD remains unclear. We aimed to (i) compare the response of turning performance while walking (180° and 360° turns) to visual cues in people with PD with and without FoG; and (ii) examine the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(15 citation statements)
references
References 38 publications
0
15
0
Order By: Relevance
“…This is an important finding as it shows that underlying visuo-cognitive mechanisms may be different in Parkinson’s compared to controls and within freezer versus non-freezer sub-groups. 48,54…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is an important finding as it shows that underlying visuo-cognitive mechanisms may be different in Parkinson’s compared to controls and within freezer versus non-freezer sub-groups. 48,54…”
Section: Discussionmentioning
confidence: 99%
“…Visuo-cognitive processes, particularly attentional processing, has been implicated in visual cue response in PwPD in our previous research. 23,25,26,28,48 To examine the influence of attention, the present study used attentional distraction through dual tasking, which was found to have no significant effect on any of the eye movement outcomes when walking with visual cues compared to single-task conditions, which is similar to findings by Stuart et al 25 Visual cues may reduce the visuo-cognitive processing of the environment that is required when walking in PwPD which allows specific focus on task relevant areas of interest (lines on the floor) and frees attentional resources to be applied to concurrent tasks (ie, the dual-task). 49…”
Section: Visual Exploration When Walking: Response To Visual Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Below, data are reported as mean ± SD. Seven trials (Mancini et al, 2018;Spildooren et al, 2017;Spildooren et al, 2012;Nieuwboer et al, 2009;Tang et al, 2017;Willems et al, 2007;Das et al, 2022) assessed cueing effectiveness on FOG exclusively during turning tasks. Plus, five studies (Arias and Cudeiro, 2010;Bryant et al, 2010;Gál et al, 2019;Holmes et al, 2015;Sijobert et al, 2017), already included in the previous section, reported also data on turning performance.…”
Section: Studies Overviewmentioning
confidence: 99%
“…Men:women ratio was about 2:1 (122:71), and sample sizes ranged from 6 to 68. Seven studies (Arias and Cudeiro, 2010;Bryant et al, 2010;Gál et al, 2019;Holmes et al, 2015;Nieuwboer et al, 2009;Willems et al, 2007;Das et al, 2022) assessed FOG severity using FOGQ (score: 14.5 ± 4.7). Disease duration was 10.2 ± 5.9 years, and H&Y scale ranged from II to IV.…”
Section: Studies Overviewmentioning
confidence: 99%